Experiencia de la atención desde la Teleorientación en el centro de atención psicológica de la Universidad Antonio Nariño, durante el segundo semestre del 2020 (Hilo Analítico, 2022)
The purpose of this article is to describe the experience that was had during the second semester of 2020 in the exercise of the teleorientation modality given the pandemic context due to covid 19 that made it impossible to provide face-to-face care for users at the Psychological Care Center of the Antonio University Nariño (CAP). The experience was systematized by the psychologists in training through field diaries. The information was analyzed through matrices that interpreted categories previously determined by the CAP professional team. It is evident that tele-guidance has marked coincidences with face-to-face care, especially the importance of the professional relationship and the implementation of interventional techniques, which encourage the achievement of consultation objectives. In particular, from the systemic approach, externalization, metaphors, managerial tasks and reflective questions are shown as effective techniques to generate new perspectives on the situations that afflict the consultants. The role of the care teacher as a co-constructor of said process is highlighted.